Strategies for working with first time marathon runners - Carter, L.; Coumbe-Lilley, J.; Anderson, B. (The Sport Journal, 2016)
Marathon running has increased in popularity and first time participants. Novice marathon runners are often highly motivated with positive attitudes at the start of their training. However, they are often unprepared for the mental and emotional demands of training and the race itself. This paper discusses the common psychological experience of "hitting the wall" and a range of challenges a novice might face on their way to race completion. A case example shows how a marathon runner might prepare to complete a marathon race and a multi-modal mental skills training approach is recommended as a complementary race preparation strategy to physical and technical preparation.